Dari al-Qur’an ke Hizbut Tahrir: Evolusi Makna Khilafah dalam Pemikiran Taqiyuddin al-Nabhani - Khotim, Khusnul; Wulandari, Maharani (Contemporary Quran, 2022)
The concept of khilafah in Islamic thought has sparked considerable debate and conflict, particularly following the rise of the Hizbut Tahrir (HT) movement, which advocates for the establishment of a global Islamic government based on Taqiyuddin al-Nabhani's interpretation of khilafah. This study aims to trace the evolution of the meaning of khilafah from its origins in the Qur'an to its modern interpretation by al-Nabhani. Utilizing Julia Kristeva's intertextuality approach, the study explores how these changes in meaning occur and identifies the sources that have influenced al-Nabhani's thought. The findings indicate that the concept of khilafah in the Qur'an fundamentally denotes representation, applicable to both humans as God's vicegerents on earth and within a governmental framework. Nevertheless, the Qur'an does not provide explicit, detailed guidelines regarding the khilafah as a system of governance. Al-Nabhani reinterprets khilafah as a government founded on Islamic Shari'ah, structured around four primary pillars, and intended to have a global reach. The study reveals significant shifts in the meaning of khilafah, characterized by processes of transformation, modification, and expansion, reflecting the context and ideological perspectives that al-Nabhani introduces. These shifts are marked by the ideologeme of transposition, illustrating the adaptation of the concept to fit new ideological frameworks and contexts.